2016
DOI: 10.1007/5584_2016_32
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of FET Proteins as a Pathological Change in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease that is characterized by the formation of abnormal inclusions in neurons. While the pathomechanism of ALS remains obscure, a number of proteins have been identified in the inclusion bodies, and the pathological roles of RNA-binding proteins have been increasingly emphasized. Among those, the FET proteins (FUS, EWSR1, TAF15) were recently identified as RNA-binding proteins in pathological inclusions of ALS and other neurodegenerative diseases; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 76 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…396 The FUS gene is positioned within chromosome 16 (its cytogenic location is 16p11. 397,398 Human FUS (UniProt ID: P35637) contains several distinct functional domains including a RNA-recognition motif and a highly-conserved C-terminal NLS. 395 This C-terminal domain is a hot-spot for the identified ALS-related mutations.…”
Section: Structural Properties Of Fusmentioning
confidence: 99%
“…396 The FUS gene is positioned within chromosome 16 (its cytogenic location is 16p11. 397,398 Human FUS (UniProt ID: P35637) contains several distinct functional domains including a RNA-recognition motif and a highly-conserved C-terminal NLS. 395 This C-terminal domain is a hot-spot for the identified ALS-related mutations.…”
Section: Structural Properties Of Fusmentioning
confidence: 99%
“…However, to date, the precise cellular components and related mechanisms damaged by abnormally expressed proteins have remained unclear (Almad et al, 2016;Clark et al, 2016;Furukawa & Tokuda, 2017;Guerrero et al, 2016;Kamelgarn et al, 2016;Martin & Chang, 2012;Prpar Mihevc et al, 2016;Z.-D. Zhou et al, 2017). The GO enrichment analysis indicated that the abnormally expressed proteins were extensively distributed in various cellular components, the most relevant of which were the muscle-related components, including the contractile fiber, the striated muscle thin filament and myofibril, and the axon-related components, such as the paranode and juxtaparanode regions of the axon (Table 1) (Almad et al, 2016;Clark et al, 2016;Furukawa & Tokuda, 2017;Guerrero et al, 2016;Kamelgarn et al, 2016;Martin & Chang, 2012;Prpar Mihevc et al, 2016;Z.-D. Zhou et al, 2017). These findings suggested that lesions of muscle-and axon-related proteins were a key pathological basis of ALS.…”
Section: Kegg Pathways Involving Differently Expressed Proteins In Th...mentioning
confidence: 99%
“…Interestingly, recent reports have shown that RNA-binding proteins that are targets of arginine dimethylation demonstrate abnormal aggregation or mislocalization in the motor neurons of sporadic ALS patients [4][5][6][7], indicating the involvement of abnormal arginine dimethylation in the pathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…It is hence hypothesized that increased CSF ADMA levels might reflect the hypermethylation of RNA‐binding proteins in the spinal motor neurons and surrounding glial cells of ALS disease patients. Interestingly, recent reports have shown that RNA‐binding proteins that are targets of arginine dimethylation demonstrate abnormal aggregation or mislocalization in the motor neurons of sporadic ALS patients [ 4 , 5 , 6 , 7 ], indicating the involvement of abnormal arginine dimethylation in the pathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 99%